Dysfunctional American Family and Spiritual Decay in Edward Albee’s Me, Myself and I - Habeeb Lateef Kadhim AL-Qassab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This research is an attempt to present a complete explanation of Edward Albee’s Me, Myself and I through applying the deconstructive theory in order to generate a better understanding of its text and thoughtful themes. According to this theory, language as a significant means of interaction does not embrace merely one meaning. This multiplicity of meanings strengthens the importance of language in Albee’s theater of the absurd. For Jacques Derrida as a French deconstructionist, the concept of "différance" plays an imperative role in the language’s multiple explanations and implications. Also, binary opposition is proven to be a significant concept, which regards such differences as central to the language, human attitude, and culture. It is shown in this study that language of Albee’s play does not have a fixed meaning. In fact, it is found that language in Albee’s Me, Myself and I is a highly significant feature which assists the readers to comprehend the absurd, vague, and formless lives of his American characters. Thus, benefitting from différance discloses the absurdities, roughness, and messiness of American society.